An Energy-Efficient Clustering Algorithm for Underwater Acoustic Sensor Networks - Xia Li; Yongqian Wang; Jingjin Zhou (2012 International Conference on Control Engineering and Communication Technology, 2012)
Energy limited has an important effect on underwater acoustic sensor network (UASN). It has been a key and primary issue to develop an effective algorithm for reducing energy consumption of UASN. In this paper, a new clustering algorithm based on low-energy adaptive clustering hierarchy (LEACH) protocol is proposed. The algorithm combines the factor of the cluster head's position, meanwhile, it involves not only the energy consumption between member nodes and cluster heads but also the energy consumption between cluster heads and base station when the member nodes choose which cluster to join in. Simulation results show that the new algorithm can balance the size of the cluster and the node's energy consumption, and reduce the total energy consumption of the network effectively.